Distributed clustering-based sensor fault diagnosis for HVAC systems - Boem,F; Reci,R; Cenedese,A; Parisini,T (IFAC / Elsevier, 2017)
The paper presents a distributed Sensor Fault Diagnosis architecture for Industrial Wireless Sensor Networks monitoring HVAC systems, by exploiting a recently proposed distributed clustering method. The approach allows the detection and isolation of multiple sensor faults and considers the possible presence of modeling uncertainties and disturbances. Detectability and isolability conditions are provided. Simulation results show the effectiveness of the proposed method for an HVAC system.